Economic burden of PTSD in the UK: a systematic review and economic analysis - Siddhartha Bandyopadhyay; Paul Montgomery-Marks; Clio Belle Weisman; Tamoghna Bose (BMJ Open, 2025)
Objectives Post-traumatic stress disorder (PTSD) constitutes a significant anxiety disorder that exerts substantial societal and familial impacts, while concurrently imposing an additional as well as a substantial burden on the healthcare system. Beyond the direct expenses incurred in its treatment, PTSD also gives rise to broader economic costs. The details of these costs in the UK are currently, we believe, unknown.Design Our methodology was developed collaboratively with a collaborative advisory group of clinicians, patients, carers and other stakeholders. A comprehensive search strategy was devised to identify articles, including systematic reviews evaluating the economic costs linked to PTSD. We adhered to the National Institute for Health and Care Excellence checklist for economic evaluations. After applying our search strategy, the selected included papers were analysed to identify various cost categories contributing to the economic burden of PTSD.Data sources PubMed, PsycInfo, PTSDpubs, EMBASE and Google Scholar were searched from January 1990 until January 2023; the search was revised and re-run in September 2024.Eligibility criteria for selecting studies The articles must have been published originally in English and include a detailed evaluation of costs related to PTSD.Data extraction and synthesis Two independent reviewers used standardised methods to search, screen and code included papers. After applying our search strategy, selected included papers were analysed to identify various cost categories contributing to the economic burden of PTSD. Detailed information on per-contact and per-session costs of healthcare variables was obtained at 2020/2021 prices. Additionally, with the advisory group, we ensured the validity of frequencies and unit cost figures associated with variables linked to PTSD. Further, indirect socio-economic costs arising from PTSD were computed.Results By extrapolating from cost components identified, our findings indicate an average annual cost exceeding £14 780 per person. Given current 2020/2021 prevalence rates, this translates to an annual societal burden of £40 billion, a figure that does not encompass the many additional financial burdens stemming from PTSD, such as poor or inconsistent employment. This figure does not include the myriad intangible costs ranging from reduced quality of life to suicidality and countless other issues a person may suffer from as a result of PTSD. Finally, this number does not capture the breadth of impact, as it is difficult to quantify how the families, communities and social systems are adversely affected (both financially and otherwise) by the condition.Conclusion The economic and societal burden of PTSD in the UK is far greater than what extant research and common understanding indicate, as there is minimal awareness and information relating to indirect costs or ancillary effects such as discrimination, joblessness, substance use and other comorbidities. Ultimately, we found that there exists, conservatively, an annual excess societal burden of £40 billion, or approximately £14 780 per person. We demonstrated that PTSD is a significantly larger burden on society and individuals than estimated and that we are gravely underquantifying the cost of this increasingly prevalent condition.